Voice Enabled Virtual Interviewer - Chinapaka Guru Sai Kamal; Mr. Sathish Kumar (Utilitas Mathematica, 2025)
Nowadays, almost everything is equipped with technology. People can save time by using modern day technological applications in the most convenient way. Smart Interviewing System is one such software tool. An interviewing system that helps students to prepare for technical interviews. The system will be voice enabled and virtual interviewer will be Alexa Skill. The system checks the accuracy of the answers which interviewee provided by comparing them with the answers stored in MongoDB database using ChatGPT. Use of ChatGPT has reduced the human intervene and also increased the performance compared to traditional interviewing systems as GPT-3 technology include the use of many pre-trained algorithms which produce content similar to texts written by people which helps in generating huge question bank and also helps in checking similarity of answers accurately.